Survey of direct medical costs in inpatient treatment of type 2 diabetes mellitus at Nhan Dan Gia Dinh Hospital, 2024 - 2025 - Nguyet, Pham Minh; Thuy, Nguyen Thi Thu; Tung, Nguyen Van; Loc, Nguyen Van; Dung, Pham Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a common chronic disease that leads to serious complications and increases the burden of healthcare costs. Identifying the direct medical costs (DMC) of inpatient care is essential to assessing the economic burden and proposing effective management strategies. Methods: A cross-sectional descriptive study from medical records and hospital billing invoices of inpatients with T2DM at Nhan Dan Gia Dinh Hospital (GDPH) in 2025. Results: A total of 464 patients were included, with a mean age of 70.0 ± 13.4 years; the majority were female (62.9%) and elderly (76.7%). The average DMC per inpatient episode was 7,287,627 VND (95% CI: 6,353,801 - 8,221,453 VND), of which the majority was covered by health insurance (88.48%). The three largest cost components were hospital bed-day charges (24.86%), laboratory tests (22.38%), and medications (22.11%). Length of stay and number of comorbidities were significantly correlated with DMC (r = 0.868; p < 0.001). Conclusions: The average DMC per inpatient episode for T2DM at GDPH in 2025 was approximately 7.3 million VND, with nearly 90% of expenses covered by health insurance. Length of stay and disease severity were the main factors influencing treatment costs.